2012
DOI: 10.1111/j.1365-2796.2012.02519.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of atrial fibrillation in a geographically well‐defined population in Northern Sweden: implications for anticoagulation prophylaxis

Abstract: Abstract. Andersson P, Löndahl M, Abdon N-J, Terent A (Hudiksvall Hospital, Hudiksvall; Lund University, Lund; and Uppsala University, Uppsala; Sweden). The prevalence of atrial fibrillation in a geographically well-defined population in Northern Sweden: implications for anticoagulation prophylaxis. J Intern Med 2012; 272:170-176.Objectives. The aims of this study were to evaluate the community-based prevalence of atrial fibrillation (AF) in a western society using a geographically welldefined population in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 34 publications
(42 reference statements)
2
31
1
Order By: Relevance
“…This fact has been also observed in few articles [13,15,30,31]. In a recent study, it has been found a slight decrease in the AF prevalence in people older than 85 years old for both, men and women [32] but in fact that article mentioned that woman never went beyond men AF prevalence.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…This fact has been also observed in few articles [13,15,30,31]. In a recent study, it has been found a slight decrease in the AF prevalence in people older than 85 years old for both, men and women [32] but in fact that article mentioned that woman never went beyond men AF prevalence.…”
Section: Discussionmentioning
confidence: 70%
“…It exists a wide range of uncertainty [20,[32][33][34] around the AF studies design. It is well known that AF prevalence is considerably higher in hospitalized patients especially in internal medicine and geriatric wards (31% for patients ≥70-year-old) [35] than in primary care [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20% in recent decades) of anticoagulant drugs in Europe and North America. Over recent decades, warfarin use has ranged from 40% to 83% in European countries, while the annual stroke rate was 1% to 5% [22][23][24][25][26] ( e- Fig 5 ). Antithrombotic therapy use (essentially warfarin and aspirin) increased in the late 2000s in China, with large variations across practice.…”
Section: Discussionmentioning
confidence: 99%
“…26 Indeed, we found a high level of baseline anticoagulant use in this population (95.5%), in contrast to other reports where rates of anticoagulant use were typically 50%-65%. [27][28][29][30] Some reports have suggested that anticoagulant use is increasing among patients with atrial fibrillation in the community, partly through increased uptake of non-vitamin K antagonists. [31][32][33] We cannot exclude some sampling bias in our study: participating sites may have been more focused on atrial fibrillation management and participating patients may have been more motivated to have an active role in their health care.…”
Section: Limitationsmentioning
confidence: 99%